Extension-Block Pinning for Unstable Dorsal Proximal Interphalangeal Joint Fracture-Dislocations: A Simple, Percutaneous Technique With Reproducible Outcomes. (June 2023) - Worgul, Christopher A.; Stein, Andrew B.
Background: Proximal interphalangeal (PIP) joint fracture-dislocations can be technically challenging injuries to treat, and no technique has proven to be superior nor lead to predictably good outcomes. We describe our experience of treating unstable dorsal fracture-dislocations of the PIP joint with extension-block pinning (EBP) at our institution over a 22-year period. Methods: In all, 23 patients with 24 unstable dorsal fracture-dislocations of the PIP joint treated with EBP between January 1998 and October 2020 were identified. All patients underwent closed reduction of the PIP joint and insertion of a Kirschner wire into the proximal phalanx, creating a mechanical block. Range of motion and joint congruity were assessed at final clinic follow-up. Long-term function was assessed via completion of a Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) questionnaire. Spearman's correlation coefficient was utilized to assess if any association existed between treatment delay, pin-in-body days, or amount of articular surface involved and QuickDASH score. Results: Mean range of motion at final follow-up was 83.3° and 22 of 24 PIP joints demonstrated a congruent reduction. In all, 15 of the 23 patients completed the QuickDASH questionnaire at a median long-term follow-up of 57.5 months (range: 3-157 months). Average QuickDASH score was 18.8, indicating minimal long-term disability. No statistically significant associations were found between treatment delay, pin-in-body days, or amount of articular surface involved and QuickDASH score. Conclusions: EBP offers a simple and innovative method to treat a complex injury of the PIP joint. It is technically straightforward and cheap, and produces excellent functional outcomes with minimal long-term disability.